A new species of the genus Leptolalax (Anura: Megophryidae) from northern Thailand - Ke Jiang (2018)
A new species of the genus Leptolalax is described from Doi Saket, Chiang Mai Province, northern Thailand. The new species is distinguished from its congeners by the following combination of characters: 1) adult size large (male SVL 45.8-52.5 mm); 2) tympanum distinct; 3) skin of dorsal surface mostly smooth, with distinct tubercles on dorsal and lateral parts of the body; 4) ventrolateral glandular ridge distinct and complete; 5) lateral body and groin covered with dark brown or black spots; 6) throat, chest, and belly nearly immaculate white; and 7) bi-colored iris, upper one-third golden, and lower two-thirds gray. Molecular phylogenetic analysis of mitochondrial 16S rRNA further distinguishes it from its congeners for which sequences are available.